Effect of Influenza Vaccination of Children on Infection Rate in Hutterite Communities: Follow-Up Study of a Randomized Trial. - Biao Wang; Margaret L Russell; Lorraine Moss; Kevin Fonseca; David J D Earn; Fred Aoki; Gregory Horsman; Paul Van Caeseele; Khami Chokani; Mark Vooght; Lorne Babiuk; Richard Webby; et al. (PLoS ONE, 2016)
An earlier cluster randomized controlled trial (RCT) of Hutterite colonies had shown that if more than 80% of children and adolescents were immunized with influenza vaccine there was a statistically significant reduction in laboratory-confirmed influenza among all unimmunized community members. We assessed the impact of this intervention for two additional influenza seasonal periods.Follow-up data for two influenza seasonal periods of a cluster randomized trial involving 1053 Canadian children and adolescents aged 36 months to 15 years in Season 2 and 1014 in Season 3 who received the study vaccine, and 2805 community members in Season 2 and 2840 in Season 3 who did not receive the study vaccine. Follow-up for Season 2 began November 18, 2009 and ended April 25, 2010 while Season 3 extended from December 6, 2010 and ended May 27, 2011. Children were randomly assigned in a blinded manner according to community membership to receive either inactivated trivalent influenza vaccine or hepatitis A. The primary outcome was confirmed influenza A and B infection using RT-PCR assay. Due to the outbreak of 2009 H1N1 pandemic, data in Season 2 were excluded for analysis.For an analysis of the combined Season 1 and Season 3 data, among non-recipients (i.e., participants who did not receive study vaccines), 66 of the 2794 (2.4%) participants in the influenza vaccine colonies and 121 of the 2301 (5.3%) participants in the hepatitis A colonies had influenza confirmed by RT-PCR, for a protective effectiveness of 60% (95% CI, 6% to 83%; P = 0.04); among all study participants (i.e., including both those who received study vaccine and those who did not), 125 of the 3806 (3.3%) in the influenza vaccine colonies and 239 of the 3243 (7.4%) in the hepatitis A colonies had influenza confirmed by RT-PCR, for a protective effectiveness of 63% (95% CI, 5% to 85%; P = 0.04).Immunizing children and adolescents with inactivated influenza vaccine can offer a protective effect among unimmunized community members for influenza A and B together when considered over multiple years of seasonal influenza.Clinicaltrials.gov NCT00877396.